Improvement of Mathematics Learning Outcomes Through the Application of Group Investigation (GI) Learning Models - Nur Laila; Sholahudin Al Ayubi (Universitas Islam Jember, 2018)
The purpose of the research is to describe the students’ activities in using Group Investigation model. And than to describe the students’ learning outcome in using Group Investigation model. The kind of the research is PTK with qualitative approach. The subjects of the research are students of class VIII at MTs Raden Fatah Tarokan Banyuanyar. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative. The results of the research there is increased activity and student learning outcomes. Keywords: group Investigation, students activity, and students learning outcomes